Geographies of Risk, the Regulatory State, and the Ethic of Care. Issue 5 (2nd September 2016) - Lejano, Raul P.; Funderburg, Richard
Abstract : We examine the role of the regulatory state in the inequitable distribution of social advantages and disadvantages. To illustrate this, we examine the spatial distribution of exposures to air toxics from noxious land uses (commonly referred to as the environmental justice problem) and inquire into the nature of state action that would allow such inequity. Findings from our inquiry lead us to focus more closely on the administrative functions of the state, especially its role as a regulatory body. A case study focusing on health risks from incompatible land uses illustrates how spatial inequities result from the formally neutral rule-making actions of regulatory agencies and their particular organizational cultures. We describe the ethical basis of the regulatory state in terms of its formal, juridical, deontological underpinnings. In contrast to this stands the alternative ethical concept of care, which is inherently relational, contextual, and preferentially attentive to the needs of the vulnerable. We argue that the regulatory state can be reformed, building structures of care to better address issues of spatial inequity. We end with a discussion of how the institutional model of the caring state might be achieved in practice.